(untitled) (Journal of actual problems of jurisprudence, 2019)
There is a multitude of approaches to characterise the subject of illegal acts during bankruptcy. The author analyses and summarises the views from different scholars on the subject of illegal acts during bankruptcy, as there are different views on this issues among the legal scholars